Pesan Dakwah Akhlak Dalam Akun Instagram MDC: Analisis Semiotika Roland Barthes - Putra, Ando Adhi (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2022)
This study aims to determine the meaning of denotation, connotation, and myth in MDC Instagram posts. The method used is a qualitative method that describes the meaning of da'wah messages about morality in MDC Instagram posts using Roland Barthes' semiotic analysis of the meaning of denotation (explicit), connotative meaning (implied), the meaning of myth. The results showed that of the thirteen posts about morality posted on the MDC Instagram account from January to September 2021, there were illustrations of Islamic images, designs, and qoutes which were widely used as a means to convey da'wah messages to the public. Keywords : Message of Da'wah; Morals; Instagram; Semiotics Roland Barthes